If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -9 = 3x + y Reorder the terms: -9 + -5x = 3x + y Solving -9 + -5x = 3x + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -9 + -5x + -3x = 3x + -3x + y Combine like terms: -5x + -3x = -8x -9 + -8x = 3x + -3x + y Combine like terms: 3x + -3x = 0 -9 + -8x = 0 + y -9 + -8x = y Add '9' to each side of the equation. -9 + 9 + -8x = 9 + y Combine like terms: -9 + 9 = 0 0 + -8x = 9 + y -8x = 9 + y Divide each side by '-8'. x = -1.125 + -0.125y Simplifying x = -1.125 + -0.125y
| k-8k=0 | | -5+-x= | | 100=5x-2y+85 | | 9x+30=4x+105 | | y=(x-5i)(x+5i) | | 18x=-100-2x | | 75/c=15/8 | | 10z+9=2 | | 3x-3/x-1=2x/x | | (x*2)+(y*4)=99 | | 7.15x+16=51.1225+4x | | y=0.15x+49 | | 35=(f-32)5/9) | | 8z+2=10 | | -2-x=15 | | log(19)=0.471 | | 14.5x=19.5y | | x=6/x-1 | | x-y=117 | | W+1.6=13 | | log(19)4=0 | | (3x^3+3x^2+4x+7)+(5x^3+2x^2+x+9)= | | 7.5h=3.2 | | 7.8a+15=100.8 | | sqrt(4x+9)-8=5 | | 1/5d=72 | | 3x+2=-x-6 | | 14=n/5 | | -2w=15 | | -13m=-14-6m | | -13m=-14-6 | | 6nsquared+n-1=0 |